World Economic Survey 1968 - United Nations (United Nations, 1968)
Part one: Some Issues of Development Policy in the Coming Decade, discusses problems and policies relating to the prospective growth of population, employment and educational requirements. It also examines policies for the acceleration of agricultural and industrial growth in the coming decade, analysing the increase in domestic and external resources required for this acceleration and considering the implication for policies of both developing and developed countries. Part two: Current Economic Developments, reviews the recent trend in the world economy, analysing the developments in 1968 and offering an outlook for 1969 as it appeared in the middle of the year.